Immunity to malaria in an era of declining malaria transmission. Issue 2 (7th January 2016) - FOWKES, FREYA J. I.; BOEUF, PHILIPPE; BEESON, JAMES G.
SUMMARY: With increasing malaria control and goals of malaria elimination, many endemic areas are transitioning from high-to-low-to-no malaria transmission. Reductions in transmission will impact on the development of naturally acquired immunity to malaria, which develops after repeated exposure to Plasmodium spp. However, it is currently unclear how declining transmission and malaria exposure will affect the development and maintenance of naturally acquired immunity. Here we review the key processes which underpin this knowledge; the amount of Plasmodium spp. exposure required to generate effective immune responses, the longevity of antibody responses and the ability to mount an effective response upon re-exposure through memory responses. Lastly we identify research priorities which will increase our understanding of how changing transmission will impact on malarial immunity.